2014
DOI: 10.1136/openhrt-2014-000109
|View full text |Cite
|
Sign up to set email alerts
|

Trends in left ventricular assist device use and outcomes among Medicare beneficiaries, 2004–2011

Abstract: ObjectiveTo characterise the trends in the left ventricular assist device (LVAD) implantation rates and outcomes between 2004 and 2011 in the Medicare population. Since the approval of the HeartMate II in 2008, the use of LVADs has steadily climbed. Given the increase in LVAD use, issues around discharge disposition, post-implant hospitalisations and costs require further understanding.MethodsWe examined LVAD implantation rates and short-term and long-term outcomes among Medicare fee-for-service beneficiaries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 23 publications
(21 reference statements)
4
62
1
Order By: Relevance
“…2,3,5,7 The REMATCH trial reported a 1-year survival of 52% among LVAD recipients. 1 Among Medicare free-for-service beneficiaries hospitalized for LVAD placement, 30-day mortality was 9% and 1-year mortality was 31% in 2011, representing a substantial decrease since 2004.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,5,7 The REMATCH trial reported a 1-year survival of 52% among LVAD recipients. 1 Among Medicare free-for-service beneficiaries hospitalized for LVAD placement, 30-day mortality was 9% and 1-year mortality was 31% in 2011, representing a substantial decrease since 2004.…”
Section: Discussionmentioning
confidence: 99%
“…1 In 2008–fueled by advances in LVAD technology, scarcity of donor hearts, 1 and a growing number of patients who are ineligible heart transplantation due to comorbidity 4 –the US Food and Drug Administration approved the use of LVADs as destination therapy for advanced heart failure, paving the way for expansion in the use of these devices. 57 …”
mentioning
confidence: 99%
“…The vast majority (95%) of VADs placed in the United States are durable continuous flow left ventricular assist devices, and this code has been used to study the epidemiology of these devices. 2, 13 Patients were included regardless of whether they underwent VAD placement as destination therapy or as a bridge to transplantation. We excluded patients with a documented stroke prior to the index visit for VAD placement.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, women appear to be referred for LVAD later in their clinical course with more severe heart failure [68,69]. The rates of implant in women are significantly lower than in men; one study of Medicare beneficiaries who underwent LVAD implant between 2004 and 2011 showed only 17 % of those receiving LVADs were women [70].…”
Section: Heart Failure Epidemiologymentioning
confidence: 99%